Yurisdiksi Negara dalam Pencegahan dan Pemberantasan Illegal Fishing di Indonesia - Halimatul Maryani (Universitas Medan Area, 2019)
The purpose of this writing is to find out the jurisdiction of the regional jurisdiction, zone of national jurisdictions covering zones in the marine region, jurisdiction in relation to the utilization of natural resources for people's needs and efforts Government to prevent and eradicate perpetrators of fish theft (illegal fishing). Furthermore, to examine and analyze this research is by combining the normative and juridical juridical methods of empirical research with qualitative data. The result of the research is that illegal fishing issue is no longer a new thing to talk about, even more and more the day is growing and increasing both qualitatively and quantitatively with the form of crime increasingly Systematic conduct of these violations. Various efforts undertaken by the Government to prevent and eradicate perpetrators of fish theft (illegal fishing), among them is to supervise and protect the waters of ZEE, take strict legal action, Improve competence and empowerment of traditional fishermen, control of the sea area and so forth.